Job Search Duration and Business Preparation Duration: An Empirical Study of Micro Data in Indonesia with Cox Regression - Hendri Cahyo Dwi Safitri; Bambang Eko Afiatno (Jurnal Economia, 2020)
Abstract: This study aims to analyze the difference in job search duration and business preparation duration based on education level, training, job experience, marital status, age, and sex. The total unit of analysis used in this study is 51,112 individuals sourced from National Labor Force Survey (Sakernas) conducted in August 2017. This study applies the Survival Analysis with Cox Regression. The survival rate results show that unemployed people who prepare a business will get a job faster than their counterparts who are still looking for a job. Cox regression testing shows that education, training, marital status, and age have significantly affected job search duration in Indonesia. Meanwhile, education, training, and marital status have significantly influenced the period of business preparation in Indonesia.                                      Keywords: unemployment, job search duration, business preparation duration, cox regression, survival analysis Lama Mencari Kerja dan Lama Mempersiapkan Usaha: Studi Empiris Data Mikro di Indonesia Abstrak: Penelitian ini bertujuan untuk menganalisis perbedaan lama mencari kerja dan lama mempersiapkan usaha dilihat dari tingkat pendidikan, pelatihan, pengalaman kerja, status perkawinan, umur, serta jenis kelamin. Total unit analisis yang digunakan sebanyak 51.112 individu yang bersumber dari data Survei Angkatan Kerja Nasional (Sakernas) Agustus 2017. Metode analisis yang digunakan adalah Survival Analysis dengan Cox Regression. Hasil survival rate menunjukkan bahwa pengangguran yang mempersiapkan usaha akan lebih cepat memperoleh pekerjaan dibandingkan dengan pengangguran yang mencari pekerjaan. Pengujian dengan cox regression menunjukkan bahwa pendidikan, pelatihan, status perkawinan, dan umur berpengaruh signifikan terhadap lama mencari pekerjaan di Indonesia. Sedangkan pendidikan, pelatihan, dan status perkawinan berpengaruh signifikan terhadap lama mempersiapkan usaha di Indonesia.                                      Kata kunci: pengangguran, lama mencari kerja, lama mempersiapkan usaha, regresi cox, analisis survival